Experimental study of formability of sheet metal in deep drawing process - Muhammad Safwan, Ismail (2011)
One of the most common outcomes in deep drawing process is a cup fractures that occur at the bottom of the cup shell. This cup fracture is cause by many parameters like blank holder force (BHF), blank diameter, friction between punch and blank, normal anisotropy of material, blank thickness and many more. The main objectives of the present study is to find the value of limiting drawing ratio (LDR) in LDR test and to predict the forming limit behaviour of sheet metal in deep drawing by construct a forming limit diagram (FLD) in FLD test for both aluminium AA1100 and copper. To determine the drawability of aluminium AA1100 and copper, LDR test with variable of blank diameters (80mm, 85mm, 90mm, 95mm and 100mm) and two set of BHF (with spring constant is 16.3 N/mm and 10 N/mm ) was utilized. On the other hand, the parameters that have used in FLD test is variable of blank thickness (1mm and 0.6mm) and surface condition of a blank using aluminium AA1100 as a constant material. In surface condition of a blank, a lubricant have been added to investigate the effect of friction between blank and punch in deep drawing process. It is observed that higher blank diameter and BHF raises the value of LDR and thus increases the drawability of aluminium AA1100 sheet and copper sheet. For FLD test, the level of FLD is increasing with increasing of blank thickness of aluminium AA1100. Besides that, the present of lubricant also raised the level of FLD and thus lessen the tendency of aluminium AA1100 sheet to rupture. From both of the experiment, it can be concluded that the formability of sheet metal is increasing due to increasing of blank diameter, blank thickness, BHF and present of lubricant. Besides that, the formability of aluminium AA1100 sheet is better compare to copper sheet.